Current role challenges in New Zealand aged residential care: the potential consequences for healthcare assistant role expansion. Issue 2 (6th May 2016) - Shannon, Kay; McKenzie-Green, Barbara
Abstract : Background: Challenges facing healthcare assistants in aged residential care are a focus of global debate. These challenges involve remuneration, education, skill mix, work conditions and organisational structures . Objectives/Aims: We enter the discussion by acknowledging current work, education and remuneration for healthcare assistants. We then consider the supervisory relationships between registered nurses (RNs), enrolled nurses (ENs) and healthcare assistants, educational levels for RNs, ENs and healthcare assistants, and the interplay between organisation and practice in aged residential care. We suggest that improving work for the healthcare assistant has the potential to lead change in all role levels .Design: Discussion paper . Conclusions/Implications for practice: We argue that adjustments to work structures, education and skill advancement of RNs, ENs and healthcare assistants could improve staff working conditions and clarify practice boundaries. The ultimate result is likely to be an improvement to quality of care and the life of residents in aged residential care.